Penguasaan Struktur Kalimat dengan Kemampuan Menulis Paragraf pada Siswa Kelas VIII SMP Negeri 10 Bandar Lampung - Alfiawati, Riska; Nurchurifiani, Eva; Wahyuningsih, Sri (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2024)
The problem discussed in this research is the relationship between mastery of sentence structure and the ability to write paragraphs. This is what becomes an obstacle for students in writing paragraphs that are not good, whereas in a good essay, paragraph by paragraph must be interconnected, and become a unified whole. As a collection of sentences, a paragraph requires coherence between sentences and must show unity of thought in expressing one idea. Meanwhile, students often write several sentences and put them in a collection or group of sentences, but talk about more than one idea that is not related to each other. Students' deficiencies in writing paragraphs are usually in the areas of vocabulary, spelling, and mastery of sentence structure and syntax. Therefore, a user of a language needs understanding to master sentence patterns in a particular language. In relation to conveying ideas in written language, someone will use an essay, which contains paragraphs or paragraphs. The population in this study was class VIII students at SMP Negeri 10 Bandar Lampung, even semester of the 2024 academic year, totaling 210 people. This research was conducted using quantitative descriptive methods. This was done because apart from presenting data, this research also used simple statistical analysis. The technique used in this research is a proportional random sample according to Stratified Proportional Random Sampling. Because the level of student ability varies from one student to another. The selection is taken randomly by showing class ranking.